Efficacy and Safety of Nicorandil in Preventing Contrast-Induced Nephropathy after Elective Percutaneous Coronary Intervention: A Pooled Analysis of 1229 Patients - Bin Yi; Shaoyan Mo; Yumei Jiang; Dingwu Yi; Jinwen Luo; Xiang Chen; Jian Rong (Journal of Interventional Cardiology)
Background. Nicorandil in reducing contrast-induced nephropathy (CIN) following elective percutaneous coronary intervention (PCI) is an inconsistent practice. This article aims to evaluate the efficacy and safety of nicorandil in preventing CIN after elective PCI. Methods. This is a pooled analysis of patients treated with elective PCI. The primary outcome was the incidence of CIN. The secondary outcomes were major adverse events, including mortality, heart failure, recurrent myocardial infarction, stroke, and renal replacement therapy. Results. A total of 1229 patients were recruited in our study. With statistical significance, nicorandil lowered the risk of CIN (odds ratio = 0.26; 95% confidence interval = 0.16–0.44; P<0.00001; I2 = 0%) in patients who underwent elective PCI. In addition, no significant differences were observed in the incidence of mortality, heart failure, recurrent myocardial infarction, stroke, and renal replacement therapy between the two groups (P>0.05). Conclusions. Our article indicated that nicorandil could prevent CIN without increasing the major adverse events. Furthermore, sufficiently powered and randomized clinical studies are still needed in order to determine the role of nicorandil in preventing CIN after elective PCI.